2019
DOI: 10.1007/s12182-019-00361-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of performance and exhaust emission characteristics of a diesel engine fuelled with Punnai biodiesel/butanol fuel blends

Abstract: This work examines the effect of butanol as an oxygenated additive to lower carbon monoxide, smoke, nitrogen oxide and hydrocarbon emissions and to improve the performance aspects of Calophyllum inophyllum (Punnai) biodiesel. Singlecylinder, oil-cooled compression ignition engines are employed in this work. Neat Punnai biodiesel (P100) is blended with butanol at 10% and 20% by volume and labelled as B10P90 and B20P80, respectively. Methanol and alkaline catalyst (KOH) were used for the transesterification proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…This shows better combustion at higher loads, which is the common trend of a CI engine. At higher loads, the amount of fuel supplied is more that leads to higher brake power and BTE (Devarajan et al 2019b). The BTE was found to be highest for diesel at all loads.…”
Section: In-cylinder Peak Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…This shows better combustion at higher loads, which is the common trend of a CI engine. At higher loads, the amount of fuel supplied is more that leads to higher brake power and BTE (Devarajan et al 2019b). The BTE was found to be highest for diesel at all loads.…”
Section: In-cylinder Peak Pressurementioning
confidence: 99%
“…At higher loads, the in-cylinder temperature is higher due to combustion of larger quantity of fuel. This in turn, increases the residence time of higher temperature leading to higher NO x emissions (Devarajan et al 2019b;Joy et al 2019). Highest NO x emissions were observed at 100% load for all selected fuels.…”
Section: Unburned Hydrocarbonsmentioning
confidence: 99%
“…As seen, the smoke emissions increase in most case with load for all tested fuel samples. This is due to the fact that a supplemental amount of fuel can be required with the identical number of air in the combustion chamber where makes the air/fuel ratios as a rich and leads to becoming incomplete combustion process and thereby higher smoke emissions in the exhaust [102]. The unmodified diesel fuel formed more smoke than that of the binary blends of 1-pentanol and diesel fuel.…”
Section: Oxygen Emissionmentioning
confidence: 99%
“…Many works reported the positive characteristics of other HA (hexanol, butanol and pentanol) and IE (DEE, DME and DMC) on diesel/biodiesel blends. Devarajan et al (2019b) investigated the appropriateness of octanol in Rice bran BD at 10%-20% in steps of 10% volume for CI engine. BD was varied from 100% to 80%, and the magnitude of octanol was varied consequently.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 10% octanol BD results in lowered NO (3.7%) and CO (6.8%) emission. Devarajan et al (2019b) employed 10% and 20% of butanol with Punnai BD in constant speed engine. Investigation revealed that the postblending of butanol to Punnai BD lowered all the emissions associated with BD.…”
Section: Introductionmentioning
confidence: 99%